ANALISIS PEMAHAMAN KONSEP IPAS MELALUI TWO-TIER-TEST PADA PEMBELAJARAN DI LUAR KELAS SD NEGERI 3 NAWANGAN - Ilma Nur Khasanah; Lina Erviana; Indah Puspitasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to analyze the conceptual understanding of fifth grade students in the subject of Natural and Social Sciences (IPAS) through the Two-Tier-Test evaluation applied in out-of-class learning. This study was based on the low conceptual understanding of students, especially in the material of light propagation. This study used a descriptive qualitative approach and was conducted at SD Negeri 3 Nawangan involving 15 students. The results showed that before this strategy, most students experienced low conceptual understanding and had difficulty understanding the basic concepts of learning. Then there was a significant change after the out-of-class learning method was used with this evaluation. Students were able to answer and provide reasons logically. This study proves that the combination of contextual learning and diagnostic evaluation is an effective strategy to improve the quality of IPAS learning.